1998
DOI: 10.1016/s0005-2728(98)00027-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron–sulfur clusters/semiquinones in Complex I

Abstract: NADH-quinone 1 oxidoreductase (Complex I) isolated from bovine heart mitochondria was, until recently, the major source for the study of this most complicated energy transducing device in the mitochondrial respiratory chain. Complex I has been shown to contain 43 subunits and possesses a molecular mass of about 1 million. Recently, Complex I genes have been cloned and sequenced from several bacterial sources including Escherichia coli, Paracoccus denitrificans, Rhodobacter capsulatus and Thermus thermophilus H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
420
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(446 citation statements)
references
References 104 publications
24
420
2
Order By: Relevance
“…It is also known that the SQ EPR signal in Complex I is rotenone-sensitive (24); the electron donor to the rst molecule of bound ubiquinone in the Complex is most probably the FeS cluster N2 (24). It is likely that this center is also the electron donor to oxygen either directly or via one-electron reduction of exogenous quinones (Fig.…”
Section: Complex Imentioning
confidence: 98%
“…It is also known that the SQ EPR signal in Complex I is rotenone-sensitive (24); the electron donor to the rst molecule of bound ubiquinone in the Complex is most probably the FeS cluster N2 (24). It is likely that this center is also the electron donor to oxygen either directly or via one-electron reduction of exogenous quinones (Fig.…”
Section: Complex Imentioning
confidence: 98%
“…These authors also proposed a possible role of cluster N1a as an anti-oxidant. N1a has, in general, a very low redox midpoint potential (E m7.0 = −370 mV) [19], and its edge-to-edge distance to FMN is 12.3Å and that to the closest iron-sulfur cluster N3 is 19.4Å. Therefore, N1a seems to play a role as a temporary electron reservoir.…”
Section: Introductionmentioning
confidence: 97%
“…In this exergonic redox reaction, the transfer of 2 electrons from one molecule of NADH to Q is coupled to the translocation of 4 protons from the negative side (abbreviated as N-side) to the positive side (P-side) of the mitochondrial inner membrane [6,32]. Complex I is the largest energy transducing complex (Molecular weight is ~1 megadalton [7], composed of 45 subunits [3] and contains 1 non-covalently bound FMN, and 8 or 9 iron-sulfur (Fe/S) clusters [19]. Recently the first atomic structure at 3.3Å resolution of the peripheral arm (hydrophilic domain) from Thermus thermophilus HB-8 complex I was determined by Sazanov and Hinchliffe [27] (See Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A flavin molecule (FMN) accepts the two reducing equivalents from the hydride formed after the heterolytic cleavage of NADH. Subsequently electrons are transferred, one at the time, via a number of EPR-detectable iron-sulphur (Fe-S) clusters (Beinert and Albracht 1982;Ohnishi 1998) to ubiquinone (Q 10 ). This process is coupled to the extrusion from the mitochondrial matrix of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups, most of them studying nonbovine systems, concluded that electron transfer from NADH to Q proceeds via FMN in the 51-kDa subunit all the way to the Fe-S cluster in the PSST subunit and from there to ubiquinone (Ohnishi 1998;Walker 1992;Friedrich 2001;Yagi and Matsuno-Yagi 2003;Hinchliffe and Sazanov 2005;Sazanov and Hinchliffe 2006;Zickermann et al 2009). Possible reasons for the discrepancy between that view and the ones presented here are reviewed in the accompanying paper.…”
Section: Introductionmentioning
confidence: 99%